The birth of big business in the United States, 1860-1914 : commercial, extractive, and industrial enterprise - Whitten, David O. (Praeger, 2006)
The economic and cultural roots of contemporary American business can be traced directly to developments in the era between the Civil War and World War I. The physical expansion of the country combined with development of transportation and communication infrastructures to create a free market of vast proportion and businesses capable of capitalizing on the accompanying economies of scale, through higher productivity, lower costs, and broader distribution. The Birth of Big Business in the United States illuminates the conditions that changed the face of American business and the national econo.